Equations for potential water savings through rainwater harvesting for different climatic conditions in Adelaide (Australia). (2018) - Paudel, Upendra; Imteaz, Monzur A.; Matos, Cristina
Among all the alternative options to minimise potable water demand, rainwater harvesting system has received the highest level of attention due to its easy collection and reuse potentials. However, available methods of quantifying potential water savings from rainwater tanks are questionable. This paper presents development of generalised equations for the quantification of potential water savings under different climatic conditions for an Australian city, Adelaide. An earlier developed daily water balance model, eTank, which can calculate potential water savings in three climatic conditions (dry, average and wet) was used for this purpose. Several relationship graphs of water savings were produced through model calculations for different input parameters.